The carbon footprint of beef transport in Colombia: Market connections and distribution networks - Castillo, Johana Marcela; González, Carlos Eduardo; Lienert, Anja; Flórez, Jesús Fernando; Bravo Parra, Aura María; Triana Ángel, Natalia; Burkart, Stefan (Frontiers Media, 2024)
Beef production is a major contributor to greenhouse gas (GHG) emissions and has therefore been placed at the center of global policy and research agendas on climate change mitigation and adaptation. However, detailed quantification of the intensity of beef’s contribution to emissions has mostly focused on the farm level. This research uses the calculation of a food miles emissions indicator to analyze the Colombian beef supply network from slaughterhouses to national consumption centers and its emissions between 2019 and 2022, including a network analysis and weighted average source distance (WASD) estimation. The results were compared with emissions from the transport of alternative animal proteins, specifically chicken and pork. The results show that the beef miles emissions indicator in Colombia is equivalent to 0.055330 kg CO 2 eq/ton of beef/km, which is higher than pork and chicken. These findings highlight the need to develop comprehensive approaches and strategies to reduce emissions from beef production, recognizing the critical role that the beef supply network, transport distances, infrastructure, and technology play in beef-related emissions.